Adapting improvement science tools and routines to build racial equity in out-of-school time STEM spaces - Iriti, Jennifer; Delale-O'Connor, Lori; Sherer, Jennifer Zoltners; Stol, Talia; Davis, Disan; Matthis, Chris; Lowry, Danielle; Legg, Alison Slinskey (Frontiers in Education, 2024)
Over the past two decades, networked improvement communities (NICs) have become popular for their collaborative, evidence-based approaches to enduring educational challenges. However, traditional improvement science has had inconsistent focus and efficacy in working on issues of racial equity. This study examines the integration of equity into improvement science through the case of the STEM PUSH Network, an NSF-funded alliance aimed at increasing racial and ethnic equity in STEM postsecondary enrollment and persistence. The STEM PUSH Network consists of 40 precollege STEM programs that strive to increase participation of Black, Latine, and Indigenous students in STEM undergraduate pathways. This paper tells the developmental story of how the network has embedded equity into its improvement practices, focusing on professional development in anti-racism and culturally sustaining pedagogy, the adoption of “living” norms, and the restructuring of inquiry cycles to prioritize marginalized voices. Initial results indicate that these efforts have significantly improved the network's equity practice and culture. The network's experiences reveal challenges such as variations in member capabilities while also demonstrating the potential for NICs to effectively incorporate equity into their practice. The STEM PUSH Network's journey offers valuable insights for other improvement networks seeking to prioritize equity, showcasing the necessity and impact of deliberate adjustments in improvement science tools and routines.